Ovine abortion by Neospora caninum: first case reported in Argentina - Hecker, Yanina (2019)
Purpose The aim of this study was to describe for the first time a natural case of ovine abortion associated with Neospora caninum in a flock with reproductive losses in Argentina. Materials and Methods The analyzed flock consisted of 256 Texel sheep, of which 134 had been mated. A single blood sample was obtained by jugular vein puncture from 220 ewes (116 adult ewes, 104 yearling ewes) and 93 lambs. Serum samples and fetal fluid were tested using the indirect fluorescence antibody test to detect antibodies against N. caninum and T. gondii. Fetal and placental tissues from aborted fetus were examined by standard gross pathology procedures and were tested using histopathology and immunohistochemistry. Moreover, DNA from fetal and placental tissues was isolated and a PCR assay to detect N. caninum, T. gondii and Chlamydia spp. was used. Results and Discussion The pregnancy rate was 89% (119/134), the abortion rate was 8.4% (10/119) whereas the perinatal mortality rate was 15% (16/109). Out of 116 adult ewes sampled, 34.48% presented anti-N. caninum antibodies. Ten ewes had aborted, and one fetus was directly submitted to the diagnostic laboratory for further processing. Antibodies against N. caninum were detected in fetal fluid and in the aborted dam. Histopathological analysis in fetal tissues showed multifocal lymphohistiocytic glossitis, diffuse mild lymphohistiocytic endocarditis, pericarditis and focally extensive myocarditis. Severe multifocal necrotizing placentitis and diffuse mild lymphohistiocytic placentitis with the presence of lymphohistiocytic vasculitis were observed in placenta. N. caninum was immunolabeled in the placenta and fetal tongue. In addition, N. caninum DNA was detected in placenta, central neural system, lung and heart of the aborted fetus. There was no evidence of other infectious abortifacients in the aborted fetus. Conclusion The present study described for the first time an ovine abortion caused by N. caninum in Argentina. Further investigations at a larger scale are required to establish the role of N. caninum as an important cause of reproductive losses in sheep flocks from the region.